LiDAR-Stabilised GNSS-IMU Platform Pose Tracking - Timothy D’Adamo; Tyson Phillips; Peter McAree (Sensors, 2022)
The requirement to estimate the six degree-of-freedom pose of a moving platform frequently arises in automation applications. It is common to estimate platform pose by the fusion of global navigation satellite systems (GNSS) measurements and translational acceleration and rotational rate measurements from an inertial measurement unit (IMU). This paper considers a specific situation where two GNSS receivers and one IMU are used and gives the full formulation of a Kalman filter-based estimator to do this. A limitation in using this sensor set is the difficulty of obtaining accurate estimates of the degree of freedom corresponding to rotation about the line passing through the two GNSS receiver antenna centres. The GNSS-aided IMU formulation is extended to incorporate LiDAR measurements in both known and unknown environments to stabilise this degree of freedom. The performance of the pose estimator is established by comparing expected LiDAR range measurements with actual range measurements. Distributions of the terrain point-to-model error are shown to improve from <semantics>0.27</semantics><semantics>m</semantics> mean error to <semantics>0.06</semantics><semantics>m</semantics> when the GNSS-aided IMU estimator is augmented with LiDAR measurements. This precision is marginally degraded to <semantics>0.14</semantics><semantics>m</semantics> when the pose estimator is operated in an a prior unknown environment.